Acceptability of digital health interventions in perioperative care: a systematic review and narrative synthesis of clinician perspectives - Stephanie Archer; Emma V Carrington; Yasmin Grant; Amal Ahmed; Chik Wai Ho (BMJ Open)
Objectives To identify themes relating to clinician acceptability of digital health intervention (DHIs) in the perioperative setting.Design Systematic review and narrative synthesis applying an inductive-deductive framework synthesis approach.Data sources Medline, Embase and Cumulative Index to Nursing and Allied Health Literature for studies published between inception and 6 March 2023.Eligibility criteria Studies with qualitative data on clinician perceptions of DHIs in the context of adult perioperative care.Data extraction and synthesis Included studies were coded inductively by a single reviewer. Codes were organised into themes based on conceptual similarities. Collaborative discussions with a second and third reviewer enabled higher-order interpretations and the emergence of subthemes. Themes and subthemes were systematically mapped onto the seven constructs of the theoretical framework of acceptability (TFA).Results A total of 3234 publications were identified, of which 18 were selected for inclusion. DHIs studied included telemedicine platforms, mobile health applications, website-based programmes and electronic health record (EHR)-integrated software. The most commonly reported TFA construct was perceived effectiveness, followed by affective attitudes, opportunity costs, ethicality, burden, intervention coherence and self-efficacy.Conclusions Clinicians’ acceptance of DHIs is primarily driven by perceived effectiveness. Optimism about the potential for DHIs to enhance care is often overshadowed by concerns about patient safety, privacy and opportunity costs. As clinicians are key gatekeepers in DHI adoption, these perspectives have a significant impact on the long-term integration of these technologies into perioperative care. Cocreation of DHIs with clinicians is required to address implementation barriers, enhancing their utilisation and uptake in the long term.PROSPERO registration number This review was conducted in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines with a protocol accessible on PROSPERO (registration number: CRD42023403205).